1993
DOI: 10.1002/jcb.240530303
|View full text |Cite
|
Sign up to set email alerts
|

Induction of osteoprogenitor cell differentiation in rat marrow stroma increases mitochondrial retention of rhodamine 123 in stromal cells

Abstract: Bone marrow stromal cells contain colony forming cells with the potential to differentiate into osteoprogenitor (OPC) cells. OPC-stimulation medium, containing dexamethasone, ascorbate, and beta-glycerophosphate is widely used to recruit OPCs in culture. Cultures were incubated 24 h with rhodamine 123 (Rho), on different days, to examine the effect of the OPC-stimulation medium on the mitochondrial membrane potential of stromal cells. Cultures grown in both ordinary medium (DMEM with 15% FCS) and OPC-stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…A study with embryonic stem cells also showed that change of electrical fields could induce embryonic stem cell membrane potential change and cell differentiation (25). Similarly, studies with rat marrow cells also showed that change of membrane potential could induce osteoprogenitor cell differentiation (26). In contrast to growth factor induced membrane hypopolarization in PC12 cells (21), we demonstrated that SW treatment induced membrane hyperpolarization of bone marrow stromal cells.…”
Section: Discussionmentioning
confidence: 82%
“…A study with embryonic stem cells also showed that change of electrical fields could induce embryonic stem cell membrane potential change and cell differentiation (25). Similarly, studies with rat marrow cells also showed that change of membrane potential could induce osteoprogenitor cell differentiation (26). In contrast to growth factor induced membrane hypopolarization in PC12 cells (21), we demonstrated that SW treatment induced membrane hyperpolarization of bone marrow stromal cells.…”
Section: Discussionmentioning
confidence: 82%
“…Although not essential for in vitro cell cultures (20), the mitochondrial activity is regulated at developmental and physiological levels (53,54), and its failure is probably involved in numerous degenerative diseases (55)(56)(57). Several nuclear genes activated by growth factors or hormones were shown to encode proteins controlling various aspects of mitochondrial metabolism: energy production (the adenine nucleotide translocator ANT2 (23), a proton/phosphate symporter (19), or cytochrome c (58)), lipid biosynthesis (the p90 glycerol-3-phosphate acyltransferase (59) or the uncoupling protein (60)), and protein import (the chaperonin hsp60 (61) or Fos effector protein-1, similar to a yeast mitochondrial protein import (22)).…”
Section: Resultsmentioning
confidence: 99%
“…This process might start with temporary coupling of oxidative-phosphorylation, reflected by a surge in membrane potential, that is, subsequently discharged [Klein et al, 1996b] and being followed by mineralization. One effect of the DEX on the coupling period is its ability to increase the membrane potential [Klein et al, 1993a], this effect of DEX is associated (as seen in Fig. 9, 4 h time point) with a surge in Bax/Bcl-2 ratio.…”
Section: Discussionmentioning
confidence: 96%